Simulation model to minimize idle time at the shipping transportation - Nur Sabihah, Ahmad (2014)
Simulation modelling is the process of creating and analysing a digital prototype of a physical model to predict its performance in the real world. Simulation modelling is used to help designers and engineers understand whether, under what conditions, and in which ways a part could fail and what loads it can withstand. The simulation is to perform the one flow to reduce idle time with the real shipping procedure. the shipping department can be the area that causes claims for loss, damager, non delivery or delay, or worse, that results in a law suit filed against your company